The Corporate Social Responsibility Disclosure Reflect Ethical and Provides A Signal in the Form of Good News - Muhammad Zaki Adriansyah Zaman; Edy Supriyono; Nurmadi Harsa Sumarta; Corina Joseph (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
ntroduction/Main Objectives: The study's novelty examines the effect of CSR disclosure on twofactors that appear within the company: internal factors in the form of earnings management bycompany management and external factors in the form of investors’ responses by investors outsidethe company. Background Problems: This study aims to test empirical evidence about the effect ofCSR disclosure on earnings management and investors’ response to the non-financial sector ofcompanies in Indonesia. Research Methods: The research data is sourced from 720 sustainabilityreports and annual report data of non-financial companies listed on the IDX during 2018-2021with a purposive sampling method. Finding/Results: The results showed that CSR disclosure hurtsearnings management and positively affects investors’ responses. Conclusion: This study indicatethat CSR disclosure reflects ethical behaviour so that financial reports are more transparent andearnings management practices will decrease, while CSR disclosure provides a signal in the formof good news that could attract investors to buy company shares.